He knew he was right [videorecording (DVD)] - Davies, Andrew, 1936-; Dimsdale, Oliver, 1972-; Fraser, Laura, 1976-; Moore, Stephen Campbell; Trollope, Anthony, 1815-1882 (Warner Home Video [distributor, 2005)
Based on the classic novel by Anthony Trollope, the story follows Louis and Emily Trevalyan. After a blissful first year of marriage, things turn darker when a roguish Colonel takes an interest in Emily that fans the flames of Louis's jealousy.